Integrasi ilmu sejarah dan ilmu geografi dalam meningkatkan kemampuan literasi sejarah mahasiswa pendidikan IPS melalui eksplorasi sejarah lokal Candi Badut - Ulfi Andrian Sari; Rusli Rusli (Universitas Negeri Malang, 2016)
In the era of globalization critical literacy skills possessed by students. Ironically literacy in Indonesia is very low. Learning history is integrated with geography expected to improve the literacy history skills of students departement social studies. Traffic literacy can make students understand the history of local history in the surrounding environment and have a critical attitude towards historical environment. This study is a qualitative research. The study was conducted at UIN Maulana Malik Ibrahim Malang. The subjects were students of the fifth semester majoring departement social studies class A. Data collection research using observation sheets, interviews, documentation and assessment indexes based on historical literacy. Analysis of the data using the model of Miles and Huberman. Based on observations conducted by researchers, the first and second meetings of learning to do without integrated with geography. The result is the literacy skills at an early stage of history to understand the events that indexes and narrative of the past. The third and fourth meetings learning is done by integrating the science of history with geography. The result is the development of historical literacy students be perfect cover 12 index are to understand the events, narratives, research skills, language history, the concept of history, an understanding of ICT, connect, debate and disagreement, the representation of expression, moral judgment, the application of scientific and historical explanation. The conclusion of this study teaching history with geography diintergasikan able to improve the literacy skills of students PIPS history through exploration of local history Temple Clowns.Keywords: history, geography, literacy http://dx.doi.org/10.17977/um022v1i22016p130